Preparation of cobalt-ruthenium nanocatalysts supported on nitrogen-doped graphene aerogel and carbon nanotubes in Fischer-Tropsch synthesis - Mohammadreza rezaei Kafrani; Ali Aghababai Beni; Zahra Pournuroz Nodeh (Arabian Journal of Chemistry, 2023)
In this study, cobalt-ruthenium nanocatalysts supported on nitrogen-doped graphene aerogel (NGA) and carbon nanotubes (CNT) were synthesized using the wet impregnation method for Fischer-Tropsch process with a cobalt to ruthenium ratio of 1:50. The synthesized catalysts underwent various characterizations such as FTIR, ICP, BET, XRD, EDX, TPR and TEM. The performance of the synthesized catalysts was compared to that of a cobalt-ruthenium nanostructured catalyst supported on NGA and CNTs. The catalysts were evaluated in a fixed-bed reactor at 25 bar, with a gas ratio H2/CO: 2 and Gas Hourly Space Velocity (GHSV) 10,000 mlg-1h-1, at temperatures of 260 °C and 280 °C. The use of NGA as a cobalt catalyst support led to a 70.5% conversion of carbon monoxide and higher methane selectivity. Conversely, the use of CNTs led to 63.7% conversion of carbon monoxide and higher selectivity towards C5+ production.